Peningkatan Arsitektur Aplikasi Sistem Lelang Agunan Perbankan Menggunakan TOGAF ADM - Setyawati, Febryana Nabilla; Abadi, Muhammad Djaka; Pratama, Andika Agus; Ernawati, Siti (Komputa : Jurnal Ilmiah Komputer dan Informatika, 2025)
The collateral auction system in banking faces challenges in terms of scalability, data security, and technology integration. This study aims to analyze and enhance the application architecture of the collateral auction system at BNI46 using the TOGAF (The Open Group Architecture Framework). The target architecture is then designed based on the Architecture Development Method (ADM) phases in TOGAF, covering aspects of Business Architecture, Information Systems Architecture, and Technology Architecture. The research methodology includes observations, interviews, and literature studies to identify weaknesses in the existing system and business requirements. TOGAF is applied as a systematic approach to designing a more flexible, secure, and efficient architecture. Technologies such as containerization, Kubernetes, and a zero-trust security model are employed to improve system efficiency. The study results indicate that the implementation of TOGAF provides a structured approach to developing an architecture that is more flexible and business-oriented. With these improvements, the collateral auction system is expected to provide better services for customers, enhance the efficiency of asset management in banking, adapt to evolving business needs, and strengthen the bank's competitiveness in the digital era.